False Computed Tomography Findings in Bilateral Choanal Atresia - Elsheikh, Ezzeddin; El-Anwar, Mohammad Waheed (International Archives of Otorhinolaryngology, 2016)
Introduction Choanal atresia (CA) is a challenging surgical problem defined as a failure in the development of communication between the nasal cavity and nasopharynx.Objective The objective of this study is to describe computed tomography (CT) findings in cases with bilateral choanal atresia.Methods The study involved performing axial and coronal non-contrast CT scanning with 2–3 mm sections on14 neonates that had bilateral CA. We used fiberoptic nasal endoscopy to confirm the diagnosis. We evaluated coronal CT to study the skull base area in such neonates.Results This study included 14 neonates with bilateral CA; with mean age of 7 ± 3.5 days. Mixed atretic plates were found in 12 (85.7%) cases while two (14.3%) had pure bony atresia. Isolated CA was detected in 9 cases (64.3%) and 5 (35.7%) cases had associated anomalies. Coronal CT showed soft tissue density in the nasal cavity that appeared to extend through an apparent defect in the nasal roof (cribriform plate), falsely diagnosed by radiologists as associated encephalocele. At the time of surgical repair, all patients showed thick tenacious mucous secretions in both nasal cavities and revealed no encephalocele. Nasal roof remained intact in all cases.Conclusion The thick secretion of bilateral CA could give a false encephalocele appearance on the CT. It is highly recommended to perform proper suction of the nasal cavity of suspected CA cases just before CT scanning.
Keywords: choanal atresia; computed tomography; neonate; encephalocele